PERANCANGAN DAN PEMBUATAN STRUKTUR MEKANIK SISTEM INSPEKSI VISI - Purnomo, Adi; Burhanuddin, Yanuar; Harun, Suryadiwansa (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
The benefit of automatic vision inspection compared with human visual inspection is also able to work all the time, more consistent and accurate. The vision inspection is also able in detecting any the defective which are difficult to find by human vision. The objectives of this research are to design and to make the mechanical structure of vision inspection system. The structure should able to carry the camera to the X and Z axis. The straightness of made structure is measured to insure the movement of each axis is also straight. The measurement done by measuring the straightness of Z axis railtrack, straightness of X axis railtrack and the parallelness was of X axis railtrack. The material of the structure was  ASTM A 500 hollow steel structure. The result of the stress was 3302666.5 N/m2  which smaller than the allowable stress of material  268895534.6 N/m. The deflection was  0.05443mm which is  smaller than the allowable deflection of material. The highest deviaton straightness of Z axis railtrack was at the point 75cm from the start point. The highest deviation straightness of X axis railtrack  is 1.4mm at the point 30cm from the first point, the highest deviation on the straighness of the parallelnes of X axis railtrack is 57cm from the first point. Several causes of the fault is detected  from the point that have expansion of the chink of every rail, it caused during the assembly (welding) process, so that material is deformed cause of the thermal that arised in the welding process and the installation of the rail that is not straight cause the railtrack is not aligned. Keywords : vision inspection, mechanical structure, straightness, parallelnes, deviation.